PENGGUNAAN MODEL PEMBELAJARAN TEAM GAMES TOURNAMENT (TGT) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA MATERI VOLUME KUBUS DAN BALOK PADA SISWA KELAS V SD NEGERI SANGGRAHAN - PURWANTI, PURWANTI (TEACHER : Jurnal Inovasi Karya Ilmiah Guru, 2023)
This research aims to determine the improvement in students' natural learning outcomes through the implementation of the Teams Garnes Tournament type cooperative learning model at SD Negeri Sanggrahan class V semester 2 of the 2019/2020 academic year with a total of 20 students. The data collected are the results of student learning outcomes in Mathematics subject areas through the Teams Games Tournament cooperative learning model. The data sources in this research were fifth grade students at Sanggrahan Wates State Elementary School and researchers who acted as teachers. The results of the student questionnaire showed that by implementing the Teams Games Tournament cooperative learning model, student learning activity increased from the initial data of 60% to 80%. From the evaluation results, it was found that the scores of students who met the KKM increased from the initial data of 55% to 80%. The changes that occur in student activity and learning outcomes can prove that the Teams Games Tournament type cooperative learning model is quite effective in improving student learning outcomes. The research results showed that the percentage of complete mathematics learning outcomes increased from 63.6%. 70% of students who completed cycle I became 80% of students who completed cycle II. Thus, the increase in student learning outcomes was 19.7%, so it is proven that the Teams Games Tournament learning model is able to improve student mathematics learning outcomes. ABSTRAKPenelitian ini bertujuan untuk mengetahui peningkatan hasil belajar maternatika siswa melalui penerapan model pembelajaran kooperatif tipe Teams Games Tournament di SD Negeri Sanggrahan kelas V semester 2 tahun pelajaran 2019/2020 yang berjumlah 20 siswa. Data yang dikumpulkan adalah hasil hasil belajar siswa pada mata pelajaran Matematika melalui model pembelajaran kooperatif Teams Games Tournament. Sumber data dalam penelitian ini adalah siswa kelas V SD Negeri Sanggrahan Wates dan peneliti yang bertindak sebagai guru. Hasil angket siswa menunjukkan bahwa dengan penerapan model pembelajaran kooperatif Teams Games Tournament keaktifan belajar siswa meningkat dari data awal 60% menjadi 80%. Dari hasil evaluasi diperoleh nilai siswa yang rnemenuhi KKM rneningkat dari data awal 55% menjadi 80%. Perubahan yang terjadi pada keaktifan dan hasil belajar siswa tersebut dapat ranger buktikan bahwa model pembelajaran kooperatif tipe Teams Games Tournament cukup efektif dalam meningkatkan hasil belajar siswa. Hasil penelitian menunjukkan bahwa persentase ketuntasan hasil belajar matematika meningkat dari 63,6%. siswa yang tuntas pada siklus I 70% menjadi 80% siswa yang tuntas pada siklus II. Dengan demikian, peningkatan hasil belajar siswa sebesar 19,7%, sehingga terbukti bahwa model pembelajaran Teams Games Tournament mampu meningkatkan hasil belajar matematika siswa.